Salinity Effects on Strategies of Glycogen Utilization in Livers of Euryhaline Milkfish (Chanos chanos) under Hypothermal Stress - Chang, Chia-Hao; Huang, Jian-Jun; Yeh, Chun-Yi; Tang, Cheng-Hao; Hwang, Lie-Yueh; Lee, Tsung-Han (Frontiers in Physiology, 2018)
The fluctuation of temperature affects many physiological responses in ectothermic organisms, including feed intake, growth, reproduction, and behavior. Changes in environmental temperatures affect the acquisition of energy, whereas hepatic glycogen plays a central role in energy supply for the homeostasis of the entire body. Glycogen phosphorylase (GP), which catalyzes the rate-limiting step in glycogenolysis, is also an indicator of environmental stress. Here, we examined the effects of salinity on glycogen metabolism in milkfish livers under cold stress. A reduction of feed intake was observed in both freshwater (FW) and seawater (SW) milkfish under cold adaptation. At normal temperature (28°C), compared to the FW milkfish, the SW milkfish exhibited greater mRNA abundance of the liver isoform of glycogen phosphorylase (Ccpygl), higher GP activity, and less glycogen content in the livers. Upon hypothermal (18°C) stress, hepatic Ccpygl mRNA expression of FW milkfish surged at 3 h, declined at 6 and 12 h, increased again at 24 h, and increased significantly after 96 h. Increases in GP protein, GP activity, and the phosphorylation state and the breakdown of glycogen were also found in FW milkfish livers after 12 h of exposure at 18°C. Conversely, the Ccpygl transcript levels in SW milkfish were downregulated after 1 h of exposure at 18°C, whereas the protein abundance of GP, GP activity, and glycogen content were not significantly altered. Taken together, under 18°C cold stress, FW milkfish exhibited an acute response with the breakdown of hepatic glycogen for maintaining energy homeostasis of the entire body, whereas no change was observed in the hepatic glycogen content and GP activity of SW milkfish because of their greater tolerance to cold conditions.